Effect of freezing-thawing on the quality changes of large yellow croaker treated by low-salt soaking during frozen storage - Bao, Hongli; Zhang, Jinsen; Li, Mingao; Chen, Yi; Mao, Chunyan; Yang, Jing; Gao, Yuanpei; Deng, Shanggui (Frontiers in Nutrition, 2023)
Introduction The production of the large yellow croaker has seasonal and regional characteristics, which is typically preserved on ice, possibly leading to its deterioration in a short time. Therefore, in this study, we focused on the effect of temperature fluctuation on the quality changes of the large yellow croaker during frozen storage. Methods In this experiment, the large yellow croaker was soaked in a low-salt solution, and physical and chemical properties, water-holding capacity, color, and protein characteristics of the muscle were investigated after repeated freeze–thaw (F–T) cycles and frozen storage. Results and discussion The results show the deterioration of muscle quality of large yellow croaker after low-salt treatment was lower than that of the salt-free soaking group. The salting treatment significantly (P < 0.05) enhanced the yield of large yellow croaker, which was 24.3% greater than the salt-free soaking group after 6 weeks of frozen storage. The microstructure of the salted muscle was more stable and maintained its cellular structure after F–T cycles and frozen storage. The b* value of the salt-free soaking group increased from b* value of the low-salt soaking group decreased from acceptable range. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis indicates the content of 17 kDa peptide decreased in the low-salt soaking group, and the peptides at 21 and 24 kDa increased during frozen storage. The results of the present study provide guidance for the optimal processing, transport, and storage of large yellow croaker, but the effect of salting on lipid oxidation and protein oxidation requires further study.